Creative and Predictive Management of Vocational Education in the Context of Social Partnership Development - Korneeva, Natalya; Uvarina, Natalya; Gnatyshina, Elena; Korneev, Dmitry (Journal of Technical Education and Training, 2023)
This research aims to theoretically substantiate the effectiveness of creative-prospective management in the professional training of contemporary youth in the context of developing social partnerships. Additionally, it aims to describe the functional model of creative-prospective management in professional education within the social partnership framework. The study involved 482 South Ural State Humanitarian-Pedagogical University students, the Russian State Vocational Pedagogical University, and the Shadrinsk State Pedagogical University. Furthermore, 100 graduates currently employed in secondary education institutions participated in the study. The following methodologies were employed in the experiment: the Mehrabian Achieving Tendency Scale (used by employers and social partners to determine the relationships between partners in social partnerships) and the modified Magomed-Eminov (1989, 2002) scale (utilized by employers and social partners to assess the quality of graduates’ professional training). A multistage quota sampling technique and a review of the modification questionnaires were used to ensure the experiment’s reliability. Respondents participated in the assessment of the effectiveness of professional education managers. The empirical research revealed synergistic connections between an expanded list of specialities and training directions associated with the differentiation of professional education and the employability of graduates in the Ural labour market. It was determined that creative and prospective management is necessary to prepare highly qualified and competitive graduates. This allowed for identifying key criteria for assessing the quality of higher education and their indicators, including the level of overall development and professional qualifications of graduates, as well as the employability of graduates in the labour market. Implementing creative and prospective management can serve as the basis for the dynamic expansion of international educational agglomerations. The development of social partnerships can increase the competitiveness of educational organisations involved in diversification processes within the international educational space. The analysed theoretical and practical positions emphasise the challenges and possible solutions associated with the system of social partnership.